Nototriche chancoae (Malvoideae, Malvaceae), una especie nueva de los Andes de Lima, Perú - Mazzei, Piero (2024)
Nototriche chancoae, a new species from the Andes of Lima, Peru, is described and illustrated. This species is related to N. glacialis, N. nigrescens and N. congesta in having flabellate laminae, hairy hypophyllum, inner side of the hairy calyx towards the apex of the lobes and corolla with tube present; It is distinguished by having wider vaginas and the outer side of the calyx with glabrous tube. The description, illustration and photographs of the new species are included, as well as a dichotomous key to the Nototriche species most similar in morphology to N. chancoae.